2014
DOI: 10.1139/apnm-2013-0380
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between exercise behavior, cardiorespiratory fitness, and cognitive function in early breast cancer patients treated with doxorubicin-containing chemotherapy: a pilot study

Abstract: The purpose of this study was to examine the relationship between self-reported exercise behavior, cardiorespiratory fitness (CRF), and cognitive function in early breast cancer patients. Thirty-seven breast cancer patients following completion of chemotherapy (median 16 months) and 14 controls were studied. Cognitive function was assessed using the Central Nervous System (CNS) Vital Signs software (CNS Vital Signs, LLC, Morrisville, N.C., USA), a computerized test battery consisting of 9 cognitive subtests. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 37 publications
1
34
0
1
Order By: Relevance
“…Exercise (approximately 4 km/d) prevented the significant decrease in performance on cognitive tasks and a reduction in hippocampal neurogenesis seen with chemotherapy administration in the nonexercise group. In humans, a recent observational study in early stage BCS treated with chemotherapy found a moderate association ( r = .47, P < .01) between self‐reported physical activity and visual memory abilities, but no association was seen with aerobic fitness …”
Section: Introductionmentioning
confidence: 99%
“…Exercise (approximately 4 km/d) prevented the significant decrease in performance on cognitive tasks and a reduction in hippocampal neurogenesis seen with chemotherapy administration in the nonexercise group. In humans, a recent observational study in early stage BCS treated with chemotherapy found a moderate association ( r = .47, P < .01) between self‐reported physical activity and visual memory abilities, but no association was seen with aerobic fitness …”
Section: Introductionmentioning
confidence: 99%
“…This recent study in 19 breast cancer survivors enrolled in a 24-week physical activity randomized controlled trial indicated that the exercise arm had greater improvements in a measure of processing speed compared with the control group. 23 Several crosssectional studies in cancer survivors using objective measures of cognition have indicated that greater physical activity is associated with several domains of cognition, including information processing speed, 24 memory, 25 executive functioning, 26 and attention. 26 These studies lend support to the hypothesis that increasing physical activity may be an effective intervention for improving cognition in breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is a strategy employed by some breast cancer survivors to attempt to decrease PCI [6], and evidence is building in support of exercise as an intervention for cancer-associated cognitive complaints [2532]. The NCCN guidelines recommend regular exercise and strength training for cancer survivors and recently added routine exercise as one of the general strategies for management of cancer-associated cognitive dysfunction [33].…”
Section: Introductionmentioning
confidence: 99%